The Challenge of Urinary Incontinence in the Elderly - Worrall, Graham (1989)
By 2021 Canada will have an enormous population older than 65 years of age. Before the wholesale introduction of programs for seniors with urinary incontinence, careful evaluation of present treatments and the extent to which they can usefully be applied in the community is necessary. We need more information about the diagnosis and treatment of urinary incontinence in the elderly and about both patient and caregiver compliance with treatment for urinary incontinence. There is a great need for research on the efficiency of programs targeted at the incontinent group and for community surveys to reassess the problem's long-term consequences.